Two Waves of Pension Reforms in Cee Countries 1998-2012 - Żukowski, Maciej (Studia Oeconomica Posnaniensia, 2013)
Since the end of the 1990s, several countries in Central and Eastern Europe (CEE) have carried out structural pension reforms, including the introduction of privately managed pension systems, a so-called second-pillar pension system. The CEE countries that implemented this type of pension system include Hungary (1998), Poland (1999), Latvia (2001), Bulgaria (2002), Croatia (2002), Estonia (2002), the Former Yugoslav Republic of Macedonia (2003), Slovakia (2005) and Romania (2008). Most CEE countries introduced structural pension reforms as part of the transformation of their socioeconomic systems following the end of communism in Central and Eastern Europe. Modernization may thus be seen as the main objective in the first wave of pension reforms. The second wave of pension reforms was closely related to the financial crisis that revealed problems of the pension systems and facilitated change. However, contrary to some accounts, no complete retreat from the funding and privatization of pension systems occurred. The second wave of pension reforms in CEE countries may be seen as the adjustment of pension systems to the circumstances. Poland was both a frontrunner of the structural reforms, introducing it in 1999, as well as making a crucial adjustment to the financial problems of the pension system by decreasing the contribution rate to the second pillar from 7.3% to 2.3% in 2011.